2020
DOI: 10.3390/rs12162656
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Sea Surface Height Using New Concepts of Kinematic GNSS Instruments

Abstract: For over 25 years, satellite altimetry observations have provided invaluable information about sea-level variations, from Global Mean Sea-Level to regional meso-scale variability. However, this information remains difficult to extract in coastal areas, where the proximity to land and complex dynamics create complications that are not sufficiently accounted for in current models. Detailed knowledge of local hydrodynamics, as well as reliable sea-surface height measurements, is required to improve and validate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…During our experiment in July 2020, the Cyclopée system was composed of a GNSS Trimble BD940 receiver with a Harxon D-Helix Antenna for absolute positioning, and a SENIX Toughsonic 14 acoustic altimeter for air-draft measurements, both installed on a gyro-stabilization arm (Figure 2). Chupin et al [13] have shown that, despite absolute bias than can arise from GNSS processing and terrestrial geodesy measurements, the Cyclopée system provides SSH measurements consistent with tide gauge observations at the centimetre level. At a fixed point, its performance is comparable to the classical GNSS buoy system widely used for satellite altimetry calibration.…”
Section: Pameli and The Cyclopée Systemmentioning
confidence: 98%
See 3 more Smart Citations
“…During our experiment in July 2020, the Cyclopée system was composed of a GNSS Trimble BD940 receiver with a Harxon D-Helix Antenna for absolute positioning, and a SENIX Toughsonic 14 acoustic altimeter for air-draft measurements, both installed on a gyro-stabilization arm (Figure 2). Chupin et al [13] have shown that, despite absolute bias than can arise from GNSS processing and terrestrial geodesy measurements, the Cyclopée system provides SSH measurements consistent with tide gauge observations at the centimetre level. At a fixed point, its performance is comparable to the classical GNSS buoy system widely used for satellite altimetry calibration.…”
Section: Pameli and The Cyclopée Systemmentioning
confidence: 98%
“…In this study, we use the USV PAMELi (Plateforme Autonome Multicapteurs pour l'Exploration du Littoral) [13,26], which allows us to extend sea-level observations offshore and even to follow altimetry tracks. Conducted at La Rochelle University, the PAMELi project aims to develop an autonomous multi-sensor platform to better monitor and understand the evolution of the coastal area [13,26]. This coastal marine drone is based on a C-CAT3 Catamaran built by L3Harris ASV, remotely controlled through Wi-Fi, GSM, or VHF communication up to several km.…”
Section: Pameli and The Cyclopée Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…An innovative aspect of this experiment was to mount the GNSS/A positioning system on an Unmanned Surface Vehicle (USV) named PAMELi (Plateforme Autonome Multicapteurs pour l'Exploration du Littoral-Autonomous Multisensor Platform for Coastal Exploration). The PAMELi project was developed by La Rochelle University for repeated and multidisciplinary monitoring of shallow coastal areas (Chupin et al, 2020). The vehicle, built by ASV, is a small battery-powered catamaran (3 m-long, 1.6 m-wide, weighting 300 kg), remotely controlled from a mother-ship or land through Wi-Fi, GSM, or VHF communications.…”
Section: The Surface Platform and Positioning Systemsmentioning
confidence: 99%